How Dialogic Vaccine Communication in the Workplace Facilitates Employee Advocacy for COVID-19 Vaccine Uptake. Issue 1 (2nd January 2023) - Tao, Weiting; Lee, Yeunjae; Li, Jo-Yun; He, Mu
ABSTRACT: Encouraging employees' vaccine uptake and motivating their vaccine advocacy are crucial steps to secure workplace health and safety during the current pandemic. Yet, how to achieve those steps remains challenging. To address this challenge, this study examines whether and how companies' vaccine communication efforts with employees, particularly dialogic communication, can motivate employees' advocacy behaviors for COVID-19 vaccine uptake. Specifically, by drawing insights from public relations, management, psychology, and health communication research, we predict that organizations' dialogic communication will enhance employees' perceptions of organizational support for vaccination, which will further increase employees' positive emotions while decreasing their negative emotions toward the vaccines. These emotional states will ultimately contribute to employees' vaccine advocacy. An online survey among 505 full-time U.S. employees supported our predictions. Our study advances public relations, organizational communication, and workplace health scholarships and practice by revealing the under-explored role of workplace communication in promoting public health.